IMPLEMENTATION OF DIVERSION IN THE CHILDREN’S CRIMINAL JURISDICTION SYSTEM BASED ON LAW NO. 11 OF 2012 - Ilham Ashari Amirullah; Hambali Thalib; Azwad Rachmat Hambali (P3M Stia Al Gazali Barru and Meraja media, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal